La imagen del destino turístico ruta del rio y la satisfacción del turista en la ciudad de Quevedo - Illesca Pincay, Perla Maritza (2022)
In the present investigation, reference is made to the analysis of the determining factors in the influx of tourists on the river route, through this investigation it is sought to analyze what are the causes of the influx of tourists on the river route. The problems of the established river route are described, emphasizing the background of the investigation. For the information process, primary and secondary sources were used to be referenced. In addition, the observation technique was used, in order to evaluate the performance of the service providers that are part of the place under study. In this way, the project proposes the planning of strategies based on the tourist experience, which serve to take measures in processes that allow increasing the satisfaction of the same.